PENGARUH PENDIDIKAN KESEHATAN TENTANG METODE KHITAN TERHADAP TINGKAT KECEMASAN ORANG TUA DI LINIK KHITAN AR-RAHMAN WONOSOBO - Arif Ustiawan; Ika Purnamasari; Romdiyah Romdiyah; Candra Dewi Rahayu (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Circumcision is an invasive procedure that aims to cut the foreskin or preposium area because the action is carried out on their child. Parents feel worried. One of the factors that influences anxiety is knowledge about the method and care of circumcision carried out by children. Objective: To determine the effect of health education about circumcision methods on the level of parents' anxiety in dealing with circumcised children at the Ar-Rahman Wonosobo circumcision clinic. This research uses a quasi-experimental quantitative research design with one group pre-test post-test with a sample of 24 respondents who were taken using purposive sampling. The research was conducted at the Ar Rahman clinic in July 2024. The characteristics analyzed in this study were aged between 31-35 years (62.5%) with female gender (58.3%) with the highest occupation being self-employed at 29.2%, followed by employees (25%) education, the majority of respondents have secondary education (48%) As many as 75% of respondents have no previous experience, before the health education was carried out, respondents who did not experience anxiety were 33.3% after it was carried out, it increased to 62.5%. The results of the paired t test obtained a significance result of 0.008. There are The significant influence of health education on the anxiety level of parents whose children undergo circumcision.